Factors affecting male-to-female ratio at birth in frozen-thawed embryo transfer cycles: a large retrospective cohort study - Du, Tong; Xie, Qin; Ye, Jing; Wang, Xindi; Qiu, Jiaxin; Yan, Zheng; Zhang, Suqun; Zhao, Dong; Lin, Jiaying; Li, Bin (Frontiers in Endocrinology, 2023)
Background: ICSI (intracytoplasmic sperm injection) led to a decreased male-to-female ratio at birth, whereas blastocyst transfer resulted in an increased male-female ratio. Limited knowledge existed regarding the impact of these risk factors on live the birth rate of each gender. This study aimed to investigate the influence of patient and treatment characteristics on the live birth rate of each gender, as well as ultimate male-to-female ratio at birth in frozen-thawed embryo transfer (FET) cycles.Method: This retrospective cohort study involved a total of 28,376 FET cycles and 9,217 subsequent deliveries, spanning from January 2003 to December 2015. The study consisted of two parts. Firstly, logistic regression models were used to determine the risk factors for the male-to-female ratio among babies born after FET. Secondly, we aimed to investigate the underlying mechanism behind the sex-ratio imbalance by analyzing data from all transfer cycles. Generalized estimated equations were employed to assess the impact of risk factors on male and female live births separately.Results: ICSI resulted in a lower proportion of male offspring compared to IVF (in vitro fertilization) (50.1% vs. 53.7%, aOR: 0.87, 95%CI: 0.80-0.96). Conversely, blastocyst transfer yielded a higher number of male offspring than cleavage-stage embryo transfer (58.7% vs. 51.6%, aOR: 1.32, 95%CI: 1.17-1.48). Upon analyzing all cycles, ICSI resulted in a diminished likelihood of male live birth in contrast to IVF (19.8% vs. 21.6%, aOR: 0.90, 95% CI:0.83-0.97). The transfer of blastocysts rather than cleavage stage embryos not only increased the chance of male live birth (26.9% vs. 20.2%,